2017
DOI: 10.4028/www.scientific.net/msf.886.117
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrometallurgical Approach to Recover Zinc and Manganese from Spent Zn-C Batteries

Abstract: This study addresses the recovery of recovery of zinc (Zn) and manganese (Mn) from spent dry cell (Zn-C battery) batteries using a hydrometallurgical approach. Every year, a significant number of Zn-C dry cell batteries are consumed and disposed worldwide. Zn-C dry cell batteries constitute more than 60% of Zn and Mn together. Higher amount of Zn and Mn present in Zn-C dry cells shows an industrial interest in recycling and recovering Zn and Mn. In this study the recovery of Zn and Mn from spent dry cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A lot of studies were found related with hydrometallurgical processes for recovery of manganese and zinc from spent zinc-carbon batteries in the literature (Shin, et al, 2009;Ferella, et al, 2008;Baba, et al, 2009;sayilgan, et al, 2010;Gęga and Walkowiak, 2011;Kursunoglu and Kaya, 2014;Buzatu, et al, 2014;Taner, et al, 2016;Abedin, et al, 2017;Chen, et al, 2017). Generally, these studies were carried out using only basic solution, acidic solution (hydrochloric acid, sulphuric acid) or reductive agents with these acid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies were found related with hydrometallurgical processes for recovery of manganese and zinc from spent zinc-carbon batteries in the literature (Shin, et al, 2009;Ferella, et al, 2008;Baba, et al, 2009;sayilgan, et al, 2010;Gęga and Walkowiak, 2011;Kursunoglu and Kaya, 2014;Buzatu, et al, 2014;Taner, et al, 2016;Abedin, et al, 2017;Chen, et al, 2017). Generally, these studies were carried out using only basic solution, acidic solution (hydrochloric acid, sulphuric acid) or reductive agents with these acid solutions.…”
Section: Introductionmentioning
confidence: 99%